ORGANIZATIONAL JUSTICE SEBAGAI DASAR PENINGKATAN KINERJA ORGANISASI (Fokus Ekonomi, 2009)
Debate about organizational justice in influencing attitude and behavior of individual in organization still be discussed. This article focused the position of organizational justice in relation  to increase organizational performance, through effectiveness of relationship between employee and supervisor, and is between employee and the organization.